2019
DOI: 10.1002/qute.201900066
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Polarization Multiphoton Controlled One‐Photon Unitary Gate Assisted by the Spatial and Temporal Degrees of Freedom

Abstract: In order to fulfill quantum information processing tasks such as quantum computation and scalable quantum networks, quantum logic gates are indispensable parts. A multiqubit logic gate can efficiently reduce the cost of physical resources and complicated operations that are necessary in the combination of fewer-qubit (e.g., two-qubit) logic gates to fulfill the same tasks. However, the construction of multiphoton quantum logic gates is a large challenge. Assisted by spatial and temporal degrees of freedom, a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Quantum logic gates, as fundamental components of complicated quantum circuits, are essential for quantum computation. [16][17][18][19][20] It is extensively proven that any quantum computing process can be completed via some elementary single-qubit operations and two-qubit entangled gates, e.g., controlled-NOT (CNOT) gate. [21] Recently, extensive attention has been raised to realize universal quantum logic gates with instinctive systems mainly including linear optics, [22][23][24][25][26] quantum dots, [27][28][29][30][31][32] superconducting circuits, [33] nitrogen vacancy centers [34][35][36][37] waveguide systems, [38][39][40][41] and neutral atoms.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Quantum logic gates, as fundamental components of complicated quantum circuits, are essential for quantum computation. [16][17][18][19][20] It is extensively proven that any quantum computing process can be completed via some elementary single-qubit operations and two-qubit entangled gates, e.g., controlled-NOT (CNOT) gate. [21] Recently, extensive attention has been raised to realize universal quantum logic gates with instinctive systems mainly including linear optics, [22][23][24][25][26] quantum dots, [27][28][29][30][31][32] superconducting circuits, [33] nitrogen vacancy centers [34][35][36][37] waveguide systems, [38][39][40][41] and neutral atoms.…”
Section: Introductionmentioning
confidence: 99%
“…First demonstrated in 1999 [6], time-bin encoding offers protection against decoherence effects in optical fibers [7], which reduce fidelities and communication distances significantly; an example being polarization-mode dispersion [8] in polarization encoding. It has been shown that universal sets of quantum operations can be performed [9][10][11], reducing the complexity compared to other linear optical quantum computing schemes [12] and the storage of time-bin qubit in solids has been demonstrated [12].…”
Section: Introductionmentioning
confidence: 99%
“…Universal entangler is established with photon pairs in arbitrary states using a parity gate with weak cross-Kerr non-linearity [36]. Polarization multi-photon controlled one-photon unitary gate is developed assisted by spatial and temporal degrees of freedom [37]. Construction of a nearly deterministic polarization Toffoli gate, single-photon controlled multi-photon unitary gate, twophoton polarization controlled arbitrary phase gate are also established using the weak cross Kerr non-linearities [38][39][40].…”
Section: Introductionmentioning
confidence: 99%